Microdispenser 3D Printing (Transactions on Additive Manufacturing Meets Medicine, 2023)
Dispensing various materials into three-dimensional structures by automatically guiding a microdispenser is used in many industrial applications. Printing a variety of biomaterials has also been successful [1]. The use of these systems for deployment in dental implantology and otolaryngology mandates a miniaturization process. In the limited workspace, a microdispenser must be capable of high-precision control since only small tolerance ranges are allowed to achieve suitable shape congruence between implant and bone for successful implantological treatment of patients [2,3]. Apart from miniaturization, dispensing highly viscous materials in small volumes presents formidable challenges [4]. Basic physical phenomena, for example, such as Rayleigh instability, which favors droplet formation of the dispensed material, and shear effects must be controlled and used in a targeted manner. Innovative concepts to develop a high-precision dispensing head suitable for highly viscous materials must be achieved to overcome these challenges and enable the usage of small three-dimensional dispensed implants during surgery inside the human body.Author’s statement Conflict of interest: Authors state no conflict of interest.References[1] Bisht B, et al. Advances in the Fabrication of Scaffold and 3D Printing of Biomimetic Bone Graft Annals of biomedical engineering 49, 2021[2] Bedrossian E. Do Dental Implant Width and Length Matter? Compent Contin Educ Dent. 2020;41:e1-e5[3] Monje A, et al. Relationship Between Primary/Mechanical and Secondary/Biological Implant Stability. Int J Oral Maxillofac Implants 2019;34:s7?s23.[4] Hachicha B, Overmeyer L Functionalization of UV-curing adhesives for surface-integrated micro-polymer optical fibers Integrated Optics 97500J, 2016
Keywords: Additive Manufacturig; Microdispenser; polymer printing; otolaryngology; Dental Implant